2011
DOI: 10.1007/s12257-011-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic co-digestion of swine manure with energy crop residues

Abstract: Anaerobic co-digestion involves the treatment of different substrates with the aim of improving the production of biogas and the stability of the process. In this research, co-digestion of swine manure (SM) and energy crop residues (ECRs) was studied. The mixtures evaluated contained SM combined with maize (Mz), rapeseed (Rs) or sunflower (Sf) residues. Batch and semi-continuous experiments were performed to determine methane (CH 4 ) yields and the behavior of reactors while co-digesting agricultural wastes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 36 publications
6
72
1
1
Order By: Relevance
“…Kaparaju et al (2009) noted that the methane percentage was 59% when the reactor was fed with only wheat straw hydrolysate, but it increased to 62.3% to 66.6% during co-digestion with cow manure. Cuetos et al (2011) and Søndergaard et al (2015) also reported methane contents of 63% to 66% and 64% to 65%, respectively, in biogas produced by the co-digestion of crop residues and manure. The reason for this may be attributed to the composition of the substrates.…”
Section: One-stage Cstr Processmentioning
confidence: 92%
See 3 more Smart Citations
“…Kaparaju et al (2009) noted that the methane percentage was 59% when the reactor was fed with only wheat straw hydrolysate, but it increased to 62.3% to 66.6% during co-digestion with cow manure. Cuetos et al (2011) and Søndergaard et al (2015) also reported methane contents of 63% to 66% and 64% to 65%, respectively, in biogas produced by the co-digestion of crop residues and manure. The reason for this may be attributed to the composition of the substrates.…”
Section: One-stage Cstr Processmentioning
confidence: 92%
“…This could be due to the use of a higher temperature (53 °C) and a much smaller particle size for the substrate (0.1 mm to 0.4 mm) in the BMP assays by Søndergaard et al (2015). Cuetos et al (2011) reported a BMP yield of about 120 mL/gVS for rapeseed straw. The lower BMP yield could be because of a higher lignin content (16.6% TS) in the substrate, compared to the lignin content of 11.7% TS in this study.…”
Section: Biochemical Methane Potential (Bmp) Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaerobic co-digestion, which is the simultaneous treatment of two or more wastes in single reactor, offers several benefits which include balancing the nutrient content [2,3], providing buffer capacity [4,5] and producing high methane yields [1,6]. Different studies have indicated that co-digesting animal manure with energy crop residues is a promising way of improving biogas production [1,7].…”
Section: Introductionmentioning
confidence: 99%